Clinical Application Value of Circulating Cell-free DNA in Hepatocellular Carcinoma - Zhang, Yuyuan; Liu, Zaoqu; Ji, Kun; Li, Xin; Wang, Caihong; Ren, Zhigang; Liu, Yang; Chen, Xinju; Han, Xinwei; Meng, Lingfang; Li, Lifeng; Li, Zhen (Frontiers in Molecular Biosciences, 2021)
Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and a leading cause of cancer-related deaths. Due to late diagnosis, early intrahepatic metastasis and nonresponse to systemic treatments, surgical resection and/or biopsy specimens remain the gold standard for disease staging, grading and clinical decision-making until now. Since invasiveness and small tissue samples were contained, the conventional tissue biopsy is unable to represent tumor heterogeneity or monitor dynamic tumor progression. For this reason, it is imperative to find a new non-invasive and easily available diagnostic tool to detect HCC at an early stage and to monitor HCC recurrence. The past decade has witnessed considerable evolution in the development of liquid biopsy technologies with the emergence of next-generation sequencing. As a liquid biopsy approach, molecular analysis of cell-free DNA (cfDNA), characterized by noninvasiveness and real-time analysis, may accurately represent the tumor burden and comprehensively reflect tumor heterogeneity. Therefore, cfDNA may be used clinically as a predictive biomarker in early diagnosis, outcome assessment, and even molecular typing. In this review, we provide an update on the recent advances made in clinical applications of cfDNA in HCC.